The review of the foreign experience on the financing of innovative medical technologies - V. V. Omelyanovskiy; I. A. Zheleznyakova; T. P. Bezdenezhnykh; M. L. Lazareva; D. V. Fedyaev (IRBIS LLC, 2020)
The article presents a review of the foreign approaches to the mechanisms of financing of medical help and innovative medical technologies with the description of the implemented financial mechanisms of stimulation of innovations in foreign systems of public healthcare. Since the system of payment for diagnosis-related groups (DRG) does not contribute to the implementation of innovations in the medical practice, the majority of countries apply additional mechanisms of financing of innovative technologies in public healthcare such as single and additional payments, and target financing that was initially not associated with a DRG model.